2010
DOI: 10.1007/s10926-010-9270-4
|View full text |Cite
|
Sign up to set email alerts
|

The Return-To-Work Coordinator Role: Qualitative Insights for Nursing

Abstract: Introduction Few studies have examined the role of RTW Coordination from the perspective of RTW Coordinator's. Furthermore there is little health specific literature on returning injured nurses to work despite the critical workforce shortages of these professionals. The study aimed to examine barriers and facilitators identified by the RTW Coordinator to returning injured nurses to work and influences on specific health sector or geographic location. The study sought to gain insights into the professional back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…Furthermore, good communication skills and the ability to safeguard confidentiality, show empathy and establish a climate of trust were identified as necessary in the context of RTW processes. A similar study published in 2014 [16] and conducted among Australian RTW coordinators involved in the development and implementation of policies and procedures within organizations operating in different sectors, yielded results consistent with those of James et al [15].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, good communication skills and the ability to safeguard confidentiality, show empathy and establish a climate of trust were identified as necessary in the context of RTW processes. A similar study published in 2014 [16] and conducted among Australian RTW coordinators involved in the development and implementation of policies and procedures within organizations operating in different sectors, yielded results consistent with those of James et al [15].…”
Section: Introductionsupporting
confidence: 82%
“…In another study, conducted in Australia with 25 RTW coordinators responsible for the return to work of injured nurses, James et al [15] identified certain points made during group discussions to the effect that personal attributes such as the ability to gain people's trust, to be a positive leader and to adequately manage conflicts were deemed as important, if not more important, than having knowledge of the worker compensation system and the impact of absences on the organization, or than having medical expertise or expertise in ergonomics. Furthermore, good communication skills and the ability to safeguard confidentiality, show empathy and establish a climate of trust were identified as necessary in the context of RTW processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the employees do not experience this is indeed happening. Difficulties on the DMP to have a central role in a multiactor arena in care are also reported in other studies [35][36][37][38][39][40][41][42]. More research on the DMP perspective is necessary.…”
Section: Discussion Of the Resultsmentioning
confidence: 83%
“…However, it is thought that it is the coordination itself, and the personal characteristics of the RTWC, rather than the specific background of the coordinator that is important to a smooth and early RTW [3, 10]. RTWCs can be employed in different ways; some are full-time RTWCs employed specifically for this role, and others take it on with only a small proportion of their work time committed to the RTWC role [11, 12]. …”
Section: Introductionmentioning
confidence: 99%